Conflict of interest in clinical research - Ghooi, Ravindra B. (Perspect Clin Res, 2015)
Increased focus on ethical review of research demands a number of improvements in the existing system. Although these are being implemented, some factors that have received less attention in the past could be examined. One of these is conflict of interest. Such conflicts could exist for investigators, ethics committee (EC) members, and even the regulators. Guidance for identification and management of conflicts has been issued by many countries and Indian rules also speak about these conflicts. Greater clarity would help investigators and ECs manage conflicts more effectively. It is admitted that conflicts cannot be done away with, but their timely identification, disclosure, and management can reduce their impact and bring more transparency and accountability to trials in this country.